A Comparative Study of Body Motion Recognition Methods for Elderly Fall Detection: A Review - Apriantoro, Roni; Setyawan, Muhammad Adriano Khairur Rizky; Lavindi, Eri Eli (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2024)
To maintain the welfare of the elderly, intensive and effective monitoring is needed to ensure their safety. Conventional elderly activity monitoring has several limitations (i.e., space and time) due to human abilities. This problem can be overcome by applying real-time monitoring methods using Wireless Body Area Networks (WBAN) and Artificial Intelligence (AI). Several methods have been used and tested, including artificial intelligence implementations from sensor data-based to computer vision-based pattern recognition for body motion classification. Several methods that have been studied show accurate results in classifying elderly body motions/gestures. However, the Human Activity Recognition (HAR) method performs better for elderly activity monitoring applications and makes fall classification more accurate.